Interethnic harmony and friendship is an important factor in the peace and prosperity of our country (Conference Zone, 2022)
This article reveals several matters on the national self-awareness of various ethnic groups, who live in Uzbekistan during the years of independence, regarding the rehabilitation of languages, national customs and traditions, conditions, which have created for the strengthening of these very habits and traditions.